Evaluation of Hospital Education Environment Perceptions of Forensic Medicine Residents - Zeybek, Volkan; Cavlak, Mehmet; Kara, Cüneyt Orhan; Tümer, Ali Rıza; Acar, Kemalettin (The Bulletin of Legal Medicine, 2021)
Background: The learning environment is key to successful education. By evaluating learning environment, strong parts and parts that need improvement of education process can be revealed. Various scales have been developed in order to evaluate issue. In this study, it was aimed to evaluate educational environments of two different departments of forensic medicine [Pamukkale University Faculty of Medicine (PAUFM) and Hacettepe University Faculty of Medicine (HUFM)] using a standard scale, compare the differences and investigate the reasons.Materials and Methods: First, resident participating in university were asked demographic information about their university, gender and academic year. Second, Postgraduate Hospital Educational Environment Measure (PHEEM) was applied. The distribution and scores for the items and subtitles were calculated.Results: Total score of the participants was 131.85 (±22.93) (perfect education environment), perception of professional autonomy subgroup mean score 46.61 (±8.04) (excellent), perception of education subgroup mean score 50.91 (±8.71) (excellent) and social support perception subgroup mean score was 34.32 (±7.11) (environment that supports learning). When scores were compared between two departments, it was observed that mean scores of HUFM were significantly higher.Conclusion: Our study is the first study in which educational environments of residents who are trained in forensic medicine are evaluated. It was determined that average scores obtained in both departments are higher than other studies conducted in different specialties in our country. It has been demonstrated that PHEEM can be used to identify and correct the problems in forensic specialty training environment and to increase quality of forensic specialty training.
Keywords: Forensic medicine residency; Postgraduate medical education; Clinical training environment